Evaluating Transfer of Certolizumab Pegol and Polyethylene Glycol into Breast Milk [28J]. Issue 1 (May 2017) - Thorp, John; Clowse, Megan; Förger, Frauke; Hwang, Caroline; Dolhain, Radboud J.E.M.; Hale, Thomas W.
Abstract : INTRODUCTION: Breastfeeding women receiving anti-TNFs for chronic inflammatory disease face concerns surrounding their potential transfer into breast milk. CRADLE was the first sponsored study to evaluate certolizumab pegol (CZP) concentrations in breast milk and estimate CZP Average Daily Infant Dose. METHODS: CRADLE (NCT02154425) studied lactating mothers (≥6 weeks postpartum) receiving CZP. After ≥3 CZP doses, breast milk samples were collected across 1 dosing period (14 days for 200 mg Q2W; 28 days for 400 mg Q4W). Optimal analytical methods were developed to determine CZP and total polyethylene glycol (PEG) levels in breast milk. RESULTS: 18 CZP-treated mothers were screened, and 17 entered the sampling period: 16 on 200 mg Q2W and 1 on 400 mg Q4W. 77/137 (56%) samples had no measurable CZP in breast milk. For 4/17 mothers, all samples were below LLQ. Estimated Average Daily Infant Dose was 0[FIGURE DASH]0.0104 mg/kg/day; median relative infant dose (RID): 0.125%. PEG was undetectable in 134/137 samples (3 had indeterminate results upon retesting). Infants of CZP-exposed mothers had a safety profile consisting of events occurring in unexposed infants of similar age. CONCLUSION: CZP was undetectable in 56% of breast milk samples. When detectable, CZP concentrations were < 3xLLQ (< 1% plasma concentration observed with therapeutic dose), indicating no/minimal CZP transfer from plasma to breast milk. RID was below 0.5% of maternal dose < 10% is considered unlikely to be of clinical concern. No transfer of PEG was observed. CZP absorption by infants via breast milk is unlikely, due to its low oral bioavailability and Fc-free structure. These findings are reassuring and support continuation of CZP treatment during breastfeeding.